Remineralization of natural early caries lesions in vitro by P11‐4 monitored with photothermal radiometry and luminescence. Issue 4 (4th January 2017) - Silvertown, Joshua D.; Wong, Bonny P. Y.; Sivagurunathan, Koneswaran S.; Abrams, Stephen H.; Kirkham, Jennifer; Amaechi, Bennett T.
Abstract: Aim: The efficacy of self‐assembling peptide P11 ‐4 to regenerate enamel in natural early caries lesions was evaluated over 50 days by photothermal radiometry and luminescence using The Canary System (CS) and The Canary Lab (CL). Methods: Baseline readings for sound and carious sites on smooth surfaces of extracted teeth were obtained by scanning with CS and CL. Teeth were then randomly assigned to a treatment group (TG, treated with P11 ‐4), a placebo group (PG, same vehicle as treatment group without P11 ‐4), or a control group (CG, no treatment). All the teeth were then placed in artificial saliva to facilitate natural remineralization, and the sites were rescanned with CS and CL at 7, 14, 30, and 50 days. Results: For carious sites in TG, mean canary numbers (CN) derived from CS decreased significantly ( P <.01) from 44±3.8 at baseline to 24±4.9 at day 50; the mean CN for the TG derived from CL also decreased significantly ( P <.05), from 65 at baseline to 45 at day 50. In contrast, no significant changes in CN were observed for carious sites in the CG or PG using either CS or CL. Conclusions: P11 ‐4 promoted the regeneration of early caries.